A novel agonist for the HGF receptor MET promotes differentiation of human pluripotent stem cells into hepatocyte‐like cells. (2nd November 2022) - Tauran, Yannick; Lereau‐Bernier, Myriam; Segard, Bertrand David; Danoy, Mathieu; Kimura, Keiichi; Shinohara, Marie; Brioude, Arnaud; Sakai, Yasuyuki; de Jonge, Hugo; Melnyk, Oleg; Vicogne, Jérôme; Leclerc, Eric
Abstract: Hepatocyte growth factor (HGF) is the natural ligand of the MET receptor tyrosine kinase. This ligand–receptor couple is essential for the maturation process of hepatocytes. Previously, the rational design of a synthetic protein based on the assembly of two K1 domains from HGF led to the production of a potent and stable MET receptor agonist. In this study, we compared the effects of K1K1 with HGF during the differentiation of hepatocyte progenitors derived from human induced pluripotent stem cells (hiPSCs). In vitro, K1K1, in the range of 20 to 200 nM, successfully substituted for HGF and efficiently activated ERK downstream signaling. Analysis of the levels of hepatocyte markers showed typical liver mRNA and protein expression (HNF4α, albumin, alpha‐fetoprotein, CYP3A4) and phenotypes. Although full maturation was not achieved, the results suggest that K1K1 is an attractive candidate MET agonist suitable for replacing complex and expensive HGF treatments to induce hepatic differentiation of hiPSCs. Abstract : Schematic dimerization and activation of MET receptor tyrosine kinase upon binding of agonist K1K1 and initiation of canonical ERK and Akt pathways.